INFLATION AND ITS CAUSES OF ORIGIN - Eshonqulov , Rakhmatillojon (Science technology&Digital finance, 2024)
This article consists in identifying inflation and its negative consequences, which are considered one of the economic processes taking place in Uzbekistan and the world, and finding measures against it. There is a brief mention of anti-inflation policies in the world and Uzbekistan.